The Academic Surgical Collaborative: A three-year review of a trainee research collaborative. (April 2018) - Pidgeon, Thomas E.; Chandrakumar, Charmilie; Al Omran, Yasser; Limb, Christopher; Thavayogan, Rachel; Gundogan, Buket; Koshy, Kiron; White, Amelia; Fowler, Alex; Agha, Riaz; ,
Abstract: Introduction: The Academic Surgical Collaborative (ASC) is a trainee research collaborative (TRC) formed in the UK in October 2014. Three years on, the achievements are presented along with advice for emerging and established TRCs. Methods: A retrospective review of internal, member-maintained ASC records was conducted. Membership numbers, PubMed indexed publications, presentations and prizes awarded were all calculated over time. Google Scholar was used to calculate citations per ASC publication. An online survey was distributed to members to ascertain member satisfaction. Results: With 62 active members (predominantly medical students) the ASC has published 33 PubMed indexed papers over three years, with a mean of 21 citations per paper (SD 89, range 0–491). 54 presentations have been delivered and eight prizes have been awarded for ASC research projects. 60% of ASC members believe the ASC delivers research that improves patient care. Key learning points for the ASC have been the use of a set of resources distributed to new members, the value of regular meetings, close mentoring throughout research projects to develop the skills of junior researchers, encouragement for junior members to present at conferences, and an ongoing focus on research conduct and improving evidence based medicine. Conclusions: The ASC has fulfilled many of its goals set out at its inception. The ASCs subsequent aims are to enhance existing research training for junior members, advances in the field of core outcome development and also multi-collaborative research. Highlights: The work of the Academic Surgical Collaborative was reviewed after three years. 33 PubMed indexed papers have been published, with a mean of 21 citations per paper. Other achievements to date are described. Learning points are provided for both developed and developing trainee research collaboratives.